2022
DOI: 10.7759/cureus.20932
|View full text |Cite
|
Sign up to set email alerts
|

Post COVID-19 Vaccine Related Cerebral Venous Sinus Thrombosis and Thrombocytopenia

Abstract: During the height of the COVID-19 pandemic, there was great relief with the global mass rollout of the Covid-19 vaccination programs. While they have proven to be safe and effective, the gradual emergence of side effects to the vaccines has undermined public trust in the vaccination program and, whilst rare, can lead to significant morbidity and mortality. The most serious was the emergence of vaccine-induced immune thrombocytopenia and thrombosis (VITT), also known as thrombosis with thrombocytopenia syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…VITT, a life-threatening emergency, has been described as a complication of adenoviral COVID-19 vaccines in the literature, although not widely reported. We have tabulated the reported cases of VITT following AstraZeneca COVID-19 vaccination in Table 2 [4][5][6][9][10][11]. The mechanism of VITT needs to be clearly defined, and it has been reported that COVID-19 vaccine-associated VITT presents 5-48 days following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…VITT, a life-threatening emergency, has been described as a complication of adenoviral COVID-19 vaccines in the literature, although not widely reported. We have tabulated the reported cases of VITT following AstraZeneca COVID-19 vaccination in Table 2 [4][5][6][9][10][11]. The mechanism of VITT needs to be clearly defined, and it has been reported that COVID-19 vaccine-associated VITT presents 5-48 days following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Other neurological complications such as Bell's palsy, acute transverse myelitis, acute demyelinating polyneuropathy, and transverse myelitis were reported, especially with mRNA vaccine[ 173 ]. Cerebral venous sinus thrombosis was also described in women of childbearing age, especially with adenovector-based vaccination[ 174 ]. The importance of developing vaccine-related autoimmune reactions or diseases is related to their impact on the intake of second dose vaccination and the morbidity rate.…”
Section: Post-vaccination Autoimmune Disordersmentioning
confidence: 99%
“…Not surprisingly, although the vaccines, in general, were massively a big relief to the stress of the people globally, and indeed did help to prevent the spread and avoidance of significant morbidity and mortality, there was an emergence of side effects. These side effects ranged from the development of rashes [ 7 ], pneumonitis [ 8 ], myositis [ 8 ], pericarditis [ 8 ], and even cerebral venous sinus thrombosis [ 9 ]. Although they were rarer occurrences, they did cause concerns about the overall effectiveness versus side effects of the new COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%